Архітектурна освіта і творчі спілки (на прикладі Львівської організації НСАУ і Львівської політехніки) - Ягольник, М. В.; Yaholnyk, M. V. (Видавництво Львівської політехніки, 2018)
Розглянуто проблему ефективного поєднання архітектурної науки, освіти й архітектурної практики, що є надзвичайно актуальним для нашої держави. Дві гілки архітектурної діяльності – навчально-наукова та практична недостатньо взаємодіють між собою. На початку ХХІ ст. питання синтезу діяльності вищої архітектурної освіти і вирішення завдання творчихспілок відображається і в публікаціяху професійній архітектурній пресі, й у програмнихдокументахНаціональної спілки архітекторів України. Однак методів та засобів поєднання в єдине гармонійне ціле завдань архітектурної освіти і науки, архітектурної практики поки що не вироблено. Як один із заходів для налагодження зв’язків архітектурної науки і практики запропоновано проведення виставки для інтегрованого й одночасного обміну інформацією з усіхділянок архітектури і будівництва – «ЕКСПО-Політехніка», яка може стати єдиним експозиційним простором для пропагування новітніхдосягнень науки і техніки, продуктів, створених науково-дослідними підрозділами Львівської політехніки.

The publication is dedicated to the problem of effective combining of architectural studies, education and architectural practice what is extremely topical for our country. At the beginning of the 21st century the issue of activity synthesis of the higher architectural education and solution of creative unions’ activity (National Union of Ukrainian Architects) found its place in publications in professional architectural press as well as in program documents of the National Union of Ukrainian Architects. However, unfortunately, the goal of finding methods and means of combining the task of architectural education and studies and task of architectural practice into one harmonized whole has not been reached. If looking at historical past, successful attempts of synthesizing two architecture branches can be highlighted: architecture as profession and architecture as art – architecture education and architecture practice. The heritage of Ivan Levynskyi – Lviv Polytechnic National University professor, pedagogue, scientist and at the same time entrepreneur, builder, public figure – is priceless. Creation of “Polytechnic Society” became extremely important for Levynskyi’s activity, among other program tasks of the society there were the following ones “...creating petitions and demands to the authorities as well as technical and industrial institutions” and “a) uniting people who work in all spheres or with their scientific and practical help to influence the development of all technology fields, put technical life in a corresponding place in the society...”. The exhibitions for integrated and simultaneous exchange of information in all fields of architecture and construction could become one of the means of organizing architectural studies and practice now and in the future. The exhibition “EXPO-Рolytechnic” could become such an event being the only exposition space for promoting brand – new science and technology achievements, products created by scientific and research departments of Lviv Polytechnic National University
Architectural education and creative units (on an example of Lviv organization of NSAU and Lviv Polytechnic)
Keywords: архітектурна діяльність; освіта і практика; конкурентоздатність; architectural activity; education and practice; competitiveness; 72.01